Pengembangan Sistem Informasi Pasien berbasis Web dengan Integrasi Google Calendar API (Studi Kasus: Praktik Mandiri Bidan Yuliani, S.ST) - Nur Eka Hartiningrum; Buce Trias Hanggara; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Praktik Mandiri Bidan (PMB) Yuliani is a midwifery service center located in Paciran District, Lamongan Regency. The number of PMB Yuliani patients always increases, in July 2021 as many as 810 patients then in August 2021 as many as 905 patients. The increase in the number of patients is not matched by an increase in services in terms of the queuing system and waiting room. The queuing system that is still manual results in the accumulation of patient queues. The limited waiting room capacity cannot accommodate the accumulation of patient queues. In addition to routine control services, patients often come not according to the predetermined control schedule. Another problem faced by PMB Yuliani is data management and patient medical records which are still done manually. This results in overcapacity of storage space, as well as difficulties in finding data when needed in a fast time. Based on these problems, the researcher intends to create a system for managing clinical service activities to be more efficient by developing a queuing web that is integrated with the google calendar API. This research uses the waterfall method, namely by conducting a literature study on the queuing system web and the integration of the Google Calendar API. Then perform analysis and system design including design using UML diagrams, as well as User Interface (UI) design, and database design using Physical Data Model (PDM). The implementation of the program code uses the PHP programming language, MySQL DBMS, and utilizes the Laravel framework. After that, the testing phase is carried out, namely blackbox testing obtaining 100% valid results, which means the system can be run properly and has fulfilled all the functional requirements that have been defined, User Acceptance Testing (UAT) gets a 90.6% value presentation so it can be concluded that the pasient system PMB Yuliani can be accepted with the results strongly agree, and compatibility testing results that the system is compatible so that the system can run well on different types of browsers.